2021
DOI: 10.21061/jvs.v7i1.227
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Treatment: A Qualitative Study of Canadian Military PTSD Clinicians

Abstract: There has been an upsurge in post-traumatic stress disorder (PTSD) research, but these efforts have not included trauma clinicians. Using a constructivist grounded research methodology, we examined clinicians' views about military PTSD, their experiences in utilizing accepted interventions, and the personal impacts of this work. Our findings indicate that clinicians struggle with conceptualizations of PTSD, accepted treatments, and the requirements of navigating the Veterans Affairs Canada (VAC) bureaucracy. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…In the civilian context, veterans reported that virtually all behaviors and choices are filtered through prevailing perceptions of PTSD. Importantly, our study shows that the struggle with the bureaucracy of Veterans Affairs and the politics of entitlement and treatment extend beyond the individual veteran through continual struggles over control (Finley, 2011;Gallagher, 2016;Whelan et al, 2021). Consistent with existing research on shame and stigma (e.g., Figley et al, 2011), veterans in our study reported shame and selfblame for failure prior to their military release about the PTSD diagnosis that left them feeling isolated from their peers.…”
Section: Discussionsupporting
confidence: 84%
“…In the civilian context, veterans reported that virtually all behaviors and choices are filtered through prevailing perceptions of PTSD. Importantly, our study shows that the struggle with the bureaucracy of Veterans Affairs and the politics of entitlement and treatment extend beyond the individual veteran through continual struggles over control (Finley, 2011;Gallagher, 2016;Whelan et al, 2021). Consistent with existing research on shame and stigma (e.g., Figley et al, 2011), veterans in our study reported shame and selfblame for failure prior to their military release about the PTSD diagnosis that left them feeling isolated from their peers.…”
Section: Discussionsupporting
confidence: 84%